The Quality of Life of Hydrocephalus Children With Shunt Implants: Literature Review - Lusiana, Deni (The Center for Disability Studies and Services Brawijaya University, 2020)
Shunt implant on hydrocephalus children can affect their quality of life, hence, it necessitates a standard instrument to evaluate the children's quality of life. This literature study provides an effective instrument to evaluate the quality of life of hydrocephalus children with shunt Implants. The findings of this literature study reveal that 10 articles fit the inclusion and exclusion criteria. The article reviews reveal several instruments used to evaluate the quality of life of hydrocephalus children with shunt implants, namely, the HOQ, PedsOL 4.0, OHS, HRQOL, mRS and SLHS questionnaires. Based on the findings the pieces of literature can become the basis for providing and developing interventions to improve the quality of life of hydrocephalus children with shunt implants